COGNITIVE SOCIAL THEORY: The Role of Cognitive Social Theory In MA Level Student Learning Activities - Ifrah Hifsy; Neviyarni; Herman Nirwana (Literasi Nusantara, 2021)
Learned is a process of changeds one's behaviored towards a certain situations caused by repeated experiences in thats situation. Where the change in behavior can not be explained. Well, in learning activities, of course, there are many theories that can be used to achieve maximum results, one of which is by using cognitive social theory. Which theorys was develop by A. Bandura. Social cognitives theory is that emphasizes the idea that most humans learng occurs in a social environment. By observed other people, humans got knowledge, rules, skills, strategies, beliefs and attitudes. In learning activities, of course, it is necessary to apply this cognitive social learning theory considering that many students learn from observing the surrounding environment, both observing teacher, parent, and the community as models. So its is important to created and explore a good environment in learning at MA level.